Experiment protocols for brain-body imaging of locomotion: A systematic review - Korivand, Soroush; Jalili, Nader; Gong, Jiaqi (Frontiers in Neuroscience, 2023)
Human locomotion is influenced by many factors, such as growth and aging, health conditions, and how active they are for their health and well-being. Notably, impaired locomotion is a high-prevalent and significant source of disability and significantly impacts the human quality of life. The uniqueness and high prevalence of human locomotion have motivated numerous research in utilizing neuroimaging technologies to understand the brain substrates, muscle responses, and motion signatures of locomotion. The outcomes of previous research cover most aspects and factors of the relationships between brain, body, and pathology. Especially with the advances in brain-body imaging techniques, most recent studies started exploring simultaneous measurements of brain activities and locomotion to examine brain-body connectivity in various experimental protocols. However, from a technical point of view, reproducing human locomotion experiments has been problematic due to the lack of protocol standardization and benchmarking tools, which ultimately impairs the evaluation of previous research quality and validation of prior understandings. This paper addresses the challenges by conducting a systematic review of existing neuroimaging studies on human locomotion, focusing on the settings of experimental protocols, such as locomotion intensity, duration, distance, adopted brain imaging technologies, and corresponding brain activation patterns. Also, this study provides practical recommendations for future experiment protocols. The results showed that EEG was the most desirable neuroimaging sensor to detect the brain activity pattern compared to fMRI, fNIRS, and PET. Furthermore, among the human locomotion tasks, walking has attracted the attention of most researchers because it is the primary locomotion and has been considered a reference. On the other hand, running was rarely studied. Also, cycling on an ergometer cycle using fNIRS with a speed of 60 rpm provides some research foundation for comparing new research. In addition, dual-task-walking tasks mainly observe the changes in the cognition source. At the same time, locomotion has been investigated for healthy individuals, which is the closest scenario to free-living activity in real-world environments. Finally, standards and available gaps for selecting a task to experiment with a specific human locomotion task are described based on the reviewed papers.